The interaction between maternal nutrient restriction and postnatal nutrient excess in an ovine model - Rhodes, Phillip Steven (2011)
Evidence from human and animal studies has highlighted the sensitivity of the developing fetus to environmental insults, such as maternal undernutrition, during gestation. These nutritional perturbations to the intrauterine milieu may engender a legacy of deleterious health consequences in adulthood. This thesis presents a series of studies which test the `mis-match‘ fetal programming theory; that is, whether a nutritionally poor diet prenatally interacts with a nutritionally excessive diet postnatally to overtly increase risk factors for adult disease. The effect of a maternal global energy restriction is contrasted against a maternal specific protein restriction, each fed during either early or late gestation. Adult offspring were subsequently exposed to an obesogenic environment (elevated feed with increased lipid content whilst restricting physical activity). Offspring metabolic flexibility and competence were assessed through routine blood samples throughout postnatal life and at 7, 18 and 24 months of age by glucose (GTT) and insulin (ITT) tolerance tests and body composition by dual energy x-ray absorptiometry. In general males appeared more susceptible to developmental programming than females at a number of timepoints. Furthermore, an increased first-phase or incremental area-under-the-insulin-response curve was observed in 1) offspring following maternal protein restriction in early gestation at 7 and 24 months of age, despite maternal protein restriction in late gestation significantly reducing birthweight and 2) in offspring exposed to maternal energy restriction during late gestation at 24 months of age in response to a GTT. Since, in both groups, the response of all offspring to an ITT (from a euglycemic baseline) was similar, infers that developmental programming in sheep followed by nutritional excess is first revealed as affecting either the pancreas (~insulin hypersecretion) or the liver (hepatic insulin resistance, reduced first-pass insulin metabolism). The studies illustrate the importance of habitual consumption of an `optimal’ balanced diet through gestation on postnatal health, especially in light of the current obesity epidemic.